PENGARUH LAMA PENYIMPANAN DAGING ITIK ALABIO DALAM REFRIGERATOR TERHADAP KUALITAS MIKROBIOLOGI, pH DAN ORGANOLEPTIK - Achmad Jaelani; Siti Dharmawati; Bahrin Noor (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Effect of Storage length  of  Alabio Meat Ducks in the refrigerator on the Quality of Microbiology , pH and organoleptic has been conducted in the Laboratory of Veterinary Research Centres (BVet) Banjarbaru . The experimental design used was Completely Randomized Design with 5 treatments and  4 replications. The variables measured were the number of microbes with total plate count (TPC) , pH and organoleptic which include color , flavor and consistency. Data were analyzed by analysis of variance (ANOVA) . As for organoleptic test using Kruskal Wallis test . In case of significantly different results , then continued by Duncan Multiple Range Test. The results showed that the Length storagealabio duck meat  in refrigerator  affect significantly to the organoleptic until 8th day refer to  a decrease in pH, color, flavor and consistency of meat Alabio, but the number of microbes was not significantly although judging the trend of his going see a decline until 4th day .